ANGPTL8 promotes adipogenic differentiation of mesenchymal stem cells: potential role in ectopic lipid deposition - Tang, Jian; Ma, Shinan; Gao, Yujiu; Zeng, Fan; Feng, Ying; Guo, Chong; Hu, Lin; Yang, Lingling; Chen, Yanghui; Zhang, Qiufang; Yuan, Yahong; Guo, Xingrong (Frontiers in Endocrinology, 2022)
Background: Ectopic lipid deposition plays a promoting role in many chronic metabolic diseases. Abnormal adipogenic differentiation of mesenchymal stem cells (MSCs) is an important cause of lipid deposition in organs. Studies have shown that serum angiopoietin-like protein 8 (ANGPTL8) levels are increased in patients with many chronic metabolic diseases (such as type 2 diabetes, obesity, and hepatic steatosis), while the role of ANGPTL8 in ectopic lipid accumulation has not been reported. Methods: We used the Gene Expression Omnibus (GEO) database to analyze the expression of ANGPTL8 in subcutaneous adipose tissue of obese patients and qPCR to analyze the expression of ANGPTL8 in the liver of high-fat diet (HFD)-induced obese mice. To explore the potential roles of ANGPTL8 in the progression of ectopic lipid deposition, ANGPTL8 knockout (KO) mice were constructed, and obesity models were induced by diet and ovariectomy (OVX). We analyzed lipid deposition (TG) in the liver, kidney, and heart tissues of different groups of mice by Oil Red O, Sudan black B staining, and the single reagent GPO-PAP method. We isolated and characterized MSCs to analyze the regulatory effect of ANGPTL8 on Wnt/β-Catenin, a key pathway in adipogenic differentiation. Finally, we used the pathway activator LiCl and a GSK3β inhibitor (i.e., CHIR99021) to analyze the regulatory mechanism of this pathway by ANGPTL8. Results: ANGPTL8 is highly expressed in the subcutaneous adipose tissue of obese patients and the liver of HFD-induced obese mice. Both normal chow diet (NCD)- and HFD-treated ANGPTL8 KO male mice gained significantly less weight than wild-type (WT) male mice and reduced ectopic lipid deposition in organs. However, the female mice of ANGPTL8 KO, especially the HFD group, did not show differences in body weight or ectopic lipid deposition because HFD could induce estrogen overexpression and then downregulate ANGPTL8 expression, thereby counteracting the reduction in HFD-induced ectopic lipid deposition by ANGPTL8 deletion, and this result was also further proven by the OVX model. Mechanistic studies demonstrated that ANGPTL8 could promote the differentiation of MSCs into adipocytes by inhibiting the Wnt/β-Catenin pathway and upregulating PPARγ and c/EBPα mRNA expression. Conclusions: ANGPTL8 promotes the differentiation of MSCs into